2021
DOI: 10.1016/j.vaccine.2021.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay and financing preferences for COVID-19 vaccination in China

Abstract: Background The COVID-19 pandemic has caused significant diseases and economic burdens in the world. Vaccines are often considered as a cost-effective way to prevent and control infectious diseases, and the research and development of COVID-19 vaccines have been progressing unprecedently. It is needed to understand individuals’ willingness to pay (WTP) among general population, which provides information about social demand, access and financing for future COVID-19 vaccination. Objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 29 publications
3
56
7
1
Order By: Relevance
“…In addition to this, the present study also revealed that only 36.9% of participants were willing to pay for the vaccine. This finding is very low when compared to previous studies done in Indonesia [ 8 ] and China [ 24 ], where 78.3% and 89.7% of their participants were willing to pay for the COVID-19 vaccine respectively. This discrepancy may be accounted for variations in the spread of the pandemic across the countries.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In addition to this, the present study also revealed that only 36.9% of participants were willing to pay for the vaccine. This finding is very low when compared to previous studies done in Indonesia [ 8 ] and China [ 24 ], where 78.3% and 89.7% of their participants were willing to pay for the COVID-19 vaccine respectively. This discrepancy may be accounted for variations in the spread of the pandemic across the countries.…”
Section: Discussioncontrasting
confidence: 77%
“…Given this, participants of this study may have lower perceived benefit of the vaccine than the participants from Indonesia due to the higher COVID-19 infection spread in Indonesia compared to Ethiopia. In this study, the median willingness to pay was 6 times lower than the median willingness to pay reported from Indonesia [ 8 ] and Malaysia [ 26 ], 2.5 times lower than the median willingness to pay reported from China [ 24 ], and the mean WTP of this study is 47.4 times lower than the mean willingness to pay reported from Chile [ 14 ]. This can be explained by the fact that the per capita income of Ethiopia is lower than those countries where the aforementioned previous studies were conducted.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…That amount was over 1.7 times higher than the mean WTP for flu vaccine among Vietnamese women of childbearing age (USD 8.5) [30], reflecting a greater perceived benefit of health gained from preventing COVID-19 than seasonal flu. However, our result was significantly lower than the amount of WTP for the COVID-19 vaccines in previous studies conducted in Indonesia (USD 57.2) [16], Malaysia (USD 30.66) [19], China (ranging from USD 28 to USD 149) [20][21][22], and Ecuador (up to USD 102.5) [24]. Besides the perception of the risk and severity of the disease, which varied across countries, we suppose another possible reason was that our study was performed when several COVID-19 vaccines were officially launched to market and information on prices of those vaccines were available while previous studies were conducted with hypothetical COVID-19 vaccines.…”
Section: Discussioncontrasting
confidence: 81%
“…People's preferences for a COVID-19 vaccine have previously been examined using discrete choice experiments (DCEs) ( Borriello et al, 2021 ; Craig, 2021 ; Dong et al, 2020 ; Leng et al, 2021 ) and other preference elicitation methods ( Motta, 2021 ; Catma and Varol, 2021 ; García and Cerda, 2020 ; Kreps et al, 2020 ; Sarasty et al, 2020 ; Tervonen et al, 2020 ; Wang et al, 2021 ). These studies investigated how the uptake of a COVID-19 vaccine was affected by characteristics such as effectiveness, location, availability, country of production, price, duration of protection and risk of side effects.…”
Section: Introductionmentioning
confidence: 99%